Kurikulum Pendidikan Pondok Pesantren Mambaus Sholihin pada Kebijakan Pemerintah di Era Society 5.0 - Vivin Nurwachidatin Nisa'; Zaenab Tri Lestari (Journal on Education, 2023)
The era of society 5.0 brings major changes to the world of education in Indonesia. There are many challenges and problems, especially for Islamic boarding schools because they are not only demanded in the religious field but also able to overcome and face the turmoil of society era 5.0. This study seeks to reveal the curriculum of the Mambaus Sholihin Islamic boarding school in the Era of Society 5.0 The method used in this study is descriptive qualitative with the type of narrative research. ra society 5.0 membawa perubahan besar bagi dunia Pendidikan di Indonesia. Banyak tantangan dan permasalahan khususnya bagi pondok pesantren karena tidak hanya dituntut di bidang keagamaan tetapi juga mampu mengatasi dan menghadapi gejolak society era 5.0. Kajian ini berusaha mengungkap kurikulum pondok pesantren Mambaus Sholihin di Era Society 5.0 Metode yang digunakan dalam penelitian ini yaitu deskriptif kualitatif dengan jenis penelitian narrative research. For data collection techniques in the form of observations, interviews and libraries. The data analysis used is in the form of interpretation. The main findings in this study stated that the education curriculum of the Mambaus Sholihin islamic boarding school followed the Ministry of Education. For non-formal education, follow the Pesantren Law No. 18 of 2019, which is based on the yellow book and Islamic dirosah. Curriculum integration is very effective as the first step of the Mambaus Sholihin Islamic boarding school in responding to the development of technology and information that is developing very quickly in the era of society 5.0.